Discovery of an Exceptionally Strong Luminescence of Polyethyleneimine‐Superparamagnetic Iron Oxide Nanoparticles. Issue 9 (7th March 2018) - Unal, Ozlem; Khodadust, Rouhollah; Durmusoglu, Emek G.; Erdem, Emre; Yagci, Mustafa Baris; Ow‐Yang, ClevaW.; Yurtsever, Ersin; Yagci Acar, Havva
Abstract: Polyethyleneimine (PEI) is rarely recognized as a luminescent polymer but is frequently used for the production of cationic nanoparticles and tagged with an organic fluorophore to be tracked optically. Herein, a strongly luminescent, branched PEI‐superparamagnetic iron oxide nanoparticle (bPEI‐SPION) without a traditional fluorophore is reported. A tremendous enhancement (1200 times) in the weak blue luminescence of bPEI is achieved only if it is adsorbed on a SPION during the synthesis of nanoparticles, which is improved further upon protonation, irreversibly. This is quite unexpected since SPIONs are strong absorbers in the visible region. All reaction parameters, different synthetic methods, as well as protonation are studied as independent factors to understand the origin of such enhancement. Detailed spectroscopic analysis and density functional theory calculations indicate that partial amine oxidation and Fe 3+ reduction takes place during the synthesis, which significantly contributes to the luminescence enhancement. In addition, PEI‐SPION exhibits excitation wavelength dependent emission and maintains its magnetic properties. Abstract : A tremendous enhancement in the intrinsic poor photoluminescence of branched polyethyleneimine (bPEI) is achieved by its in situ deposition on the surface of iron oxide nanoparticles (SPION) during the synthesis. Partial amine oxidation coupled with surface adsorption and protonation were determined as key effectors of this phenomenon. bPEI‐SPION luminesce 1200 times stronger than free PEI.